CLINICAL RECOMMENDATION TO THE DIAGNOSTICS AND TREATMENT OF HYPOPHOSPHATASIA IN CHILDREN - A. A. Baranov; L. S. Namazova-Baranova; К. V. Savostianov; Т. V. Margieva; E. A. Vishneva; G. Т. Yakhyaeva (Union of pediatricians of Russia, 2017)
Hypophosphatasia is a rare genetic disorder caused by deficiency of tissue-specific  alkaline phosphatase as a result of mutations in the ALPL gene. Depending on the form and severity of the disease, pathology may spawn in utero, in childhood or in adult age. Given functions of alkaline phosphatase, patients experience multisystem disorders: primarily changes in bone (osteoporosis, rachitic deformations,  fractures),  lung  disease  (hypoplasia  with respiratory  failure)  and  central  nervous  system  (seizures),  hypercalcemia with development of nephrocalcinosis. Without timely treatment, the disease may be harmful to life in most cases. Patients required observation of a multidisciplinary team of physicians. The only effective treatment is enzyme replacement therapy with asfotase alpha. It is also necessary to carry out symptomatic treatment and rehabilitation of patients with the use of physiotherapy and therapeutic physical training complexes of exercises.